2018
DOI: 10.1038/s41388-017-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor Hic1 maintains chromosomal stability independent of Tp53

Abstract: Hypermethylated-in-Cancer 1 (Hic1) is a tumor suppressor gene frequently inactivated by epigenetic silencing and loss-of-heterozygosity in a broad range of cancers. Loss of HIC1, a sequence-specific zinc finger transcriptional repressor, results in deregulation of genes that promote a malignant phenotype in a lineage-specific manner. In particular, upregulation of the HIC1 target gene SIRT1, a histone deacetylase, can promote tumor growth by inactivating TP53. An alternate line of evidence suggests that HIC1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Here, we showed that conditional deletion of HIC1 in the mouse mammary gland may contribute to premalignant transformation at the early stage of tumor formation, inducing the formation of hyperplastic epithelium and increased expression of the proliferative markers Ki67 and cyclin D1 in mammary gland. Mechanistically, loss of HIC1 expression in lung cancer contributes to malignant transformation through the acquisition of chromosomal instability (38), which suggests that it may also correlate with mammary gland tumorigenesis. Furthermore, it has been reported that HIC1 acts as a nuclear modulator of the Wnt-signaling pathway by recruiting TCF4 and β-catenin to HIC1 bodies to exert its suppression functions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that conditional deletion of HIC1 in the mouse mammary gland may contribute to premalignant transformation at the early stage of tumor formation, inducing the formation of hyperplastic epithelium and increased expression of the proliferative markers Ki67 and cyclin D1 in mammary gland. Mechanistically, loss of HIC1 expression in lung cancer contributes to malignant transformation through the acquisition of chromosomal instability (38), which suggests that it may also correlate with mammary gland tumorigenesis. Furthermore, it has been reported that HIC1 acts as a nuclear modulator of the Wnt-signaling pathway by recruiting TCF4 and β-catenin to HIC1 bodies to exert its suppression functions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Hyper methylated In Cancer 1 (HIC1) is a transcriptional repressor that acts as a tumor suppressor and frequently is inactivated by epigenetic silencing. It has been shown to negatively regulate the WNT signaling pathway [44,45]. Growth Factor Independence 1 (GFI1) is a zinc finger protein, which acts as a transcriptional repressor.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, HIC1 was shown to repress the SIRT1 gene promoter, thereby preventing SIRT1-mediated deacetylation and inactivation of the tumor suppressor TP53 38 . However, another way how HIC1 can suppress tumorigenesis independent of TP53 is through averting chromosomal instability 39 . Therefore, it is tempting to hypothesize that MDFIC also regulates TP53 activity and genome integrity.…”
Section: Discussionmentioning
confidence: 99%